Pengembangan Artificial Intelligence Asisten Edukasi Psikologi Berbasis Website Dengan Pendekatan Deep Learning - Mohammad Mohammad; Achsel Aldrian; Dzulqarnain Dzulqarnain (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2025)
This research presents the development of an Artificial Intelligence (AI)-based chatbot as a web-based psychological education assistant. The chatbot is designed to help users, particularly students, understand psychological issues such as academic stress, anxiety, and burnout. The model was developed using a deep learning approach based on the Transformer architecture, which enables contextual understanding and natural response generation. The research used the Prototyping method, covering stages of needs analysis, system design, deep learning model development, website implementation, and evaluation. The System Usability Scale (SUS) evaluation produced an average score of 87.5, categorized as Excellent. The system effectively provides relevant responses and contributes to improving digital psychological literacy.